Transformational Leadership Boosts Employee Performance in Indonesia - Reni Eka Putri; Sumartik (Indonesian Journal of Cultural and Community Development, 2024)
This study examines the impact of Transformational Leadership Style, Organizational Culture, and Work Climate on Employee Performance at the Community and Village Empowerment Offices in Sidoarjo District. Using a quantitative approach, data were collected from 100 employees through surveys and analyzed with multiple linear regression using SPSS version 25. Results show that all three factors positively influence employee performance, with Organizational Culture being the most significant. This research underscores the importance of enhancing organizational culture to boost employee performance, providing valuable insights for policymakers and practitioners in village empowerment. Highlight: Transformational Leadership: Positively impacts employee performance. Organizational Culture: Most significant factor affecting performance. Quantitative Analysis: Utilized surveys and regression analysis. Keywoard: Transformational Leadership, Organizational Culture, Work Climate, Employee Performance, Village Empowerment